A parametric study on hydraulic conductivity and self-healing properties of geotextile clay liners used in landfills. (1st November 2017) - Parastar, Fatemeh; Hejazi, Sayyed Mahdi; Sheikhzadeh, Mohammad; Alirezazadeh, Azam
Abstract: Nowadays, the raise of excessive generation of solid wastes is considered as a major environmental concern due to the fast global population growth. The contamination of groundwater from landfill leachate compromises every living creature. Geotextile clay liner (GCL) that has a sandwich structure with two fibrous sheets and a clay core can be considered as an engineered solution to prevent hazardous pollutants from entering into groundwater. The main objective of the present study is therefore to enhance the performance of GCL structures. By changing some structural factors such as clay type (sodium vs. calcium bentonite), areal density of clay, density of geotextile, geotextile thickness, texture type (woven vs. nonwoven), and needle punching density a series of GCL samples were fabricated. Water pressure, type of cover soil and overburden pressure were the environmental variables, while the response variables were hydraulic conductivity and self-healing rate of GCL. Rigid wall constant head permeability test was conducted on all the samples. The outlet water flow was measured and evaluated at a defined time period and the hydraulic conductivity was determined for each sample. In the final stage, self-healing properties of samples were investigated and an analytical model was used to explain the results. It was found that higher Montmorillonite content of clay, overburden pressure, needle punching density and areal density of clay poses better self-healing properties and less hydraulic conductivity, meanwhile, an increase in water pressure increases the hydraulic conductivity. Moreover, the observations were aligned with the analytical model and indicated that higher fiber inclusion as a result of higher needle-punching density produces closer contact between bentonite and fibers, reduces hydraulic conductivity and increases self-healing properties. Graphical abstract: Highlights: Structural parameters of Geotextile Clay Liner (GCL) was investigated. Both hydraulic conductivity and self-healing capacity of GCLs were investigated. Structural modifications are suggested to enhance the performance of GCLs. The phenomenon of self-healing was described by an analytical model.